Phosphorilation of histone H3 in plants - a dynamic affair - Houben, Andreas (2011)
Histones are the main protein components of chromatin: they undergo extensive post-translational modifications, particularly acetylation, methylation, phosphorylation, ubiquitination and ADP-ribosylation which modify the structural/functional properties of chromatin. Posttranslational modifications of the N-terminal tails of the core histones within the nucleosome particle are thought to act as signals from the chromatin to the cell, for various processes. Thus, in many ways histone tails can be viewed as complex protein–protein interaction surfaces that are regulated by numerous post-translational modifications. Histone phosphorylation has been linked to chromosome condensation/segregation, activation of transcription, apoptosis and DNA damage repair. In plants, the cell cycle dependent phosphorylation of histone H3 has been described; it is hyperphosphorylated at serines 10/28 and at threonines 3/11 during both mitosis and meiosis in patterns that are specifically coordinated in both space and time. Although this post-translational modification is highly conserved, data show that the chromosomal distribution of individual modifications can differ between groups of eukaryotes. Initial results indicate that members of the plant Aurora kinase family have the capacity to control cell cycle regulated histone H3 phosphorylation, and in addition we describe other potential H3 kinases and discuss their functions.